Barakeden: Les petites bonnes de Bamako - Gonin, Adeline (France : Association L’Echangeur, 2015)
Oumou left her village when she was 14 to come to work as a maid in Bamako. Endless days, humiliation, pittance…
Like hundreds of thousands of her fellows, she endures harsh life with hope for a better life. By night, these "little maids"
gather to express their resentment. Helped by a group of activists, some of them begin to organize themselves so as to
defend their rights. Meanwhile, one maid named Hawa is about to leave her village and come for the first time to the city.
Verzio Film Festival Submission
Keywords: Documentary films